2014
DOI: 10.5799/ahinjs.01.2014.03.0426
|View full text |Cite
|
Sign up to set email alerts
|

Nonfermentative gram-negative microorganisms isolated from intensive care units and their resistance profiles in a training and research hospital

Abstract: The aim of this study was to determine the pathogenic agents, which have been isolated in ICUs and determine their antimicrobial susceptibility in the first two years of our hospital. Methods: A total 368 strains (194 Pseudomonas aeruginosa, and 174 Acinetobacter baumannii) that were considered as an infectious agent and isolated from different clinical samples of hospitalized patients in intensive care units between January 2011 and December 2012 were included in the study. Conventional methods and automatize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…In a study conducted in the ICUs of a training and research hospital, Bilman et al reported carbapenem resistance rates as 85% (meropenem) and 87% (imipenem) for Acinetobacter spp. and, 35% (meropenem) and 36% (imipenem) for P.aeruginosa [20]. In another study conducted by Yolbaş et al carbapenem resistance rate for Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 93%
“…In a study conducted in the ICUs of a training and research hospital, Bilman et al reported carbapenem resistance rates as 85% (meropenem) and 87% (imipenem) for Acinetobacter spp. and, 35% (meropenem) and 36% (imipenem) for P.aeruginosa [20]. In another study conducted by Yolbaş et al carbapenem resistance rate for Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 93%
“…A. baumannii suşlarında saptanan trimetoprim-sulfametoksazol direnç oranı yurt içi ve yurt dışında yapılan farklı çalışmalarda %13,6-%100 arasında değişmektedir [7][8][9]18,20,21,[29][30][31]. Çalışmamızda trimetoprim-sulfametoksazol direnç oranı 2011 yılında %77,6 iken, 2012'de %61,6'ya ve 2013'de %46'ya kadar düşmüştür.…”
Section: Yöntemlerunclassified
“…Son yıllarda P. aeruginosa ve A. baumannii suşlarında görülen karbapenemaz üretimindeki artış, bu antibiyotiklere karşı direnci de beraberinde taşımaktadır [4,5]. Ülkemizde ve yurt dışında yapılan farklı çalışmalarda; P. aeruginosa izolatlarında imipenem direnci %15,5-78,8 ve meropenem direnci %7,5-71,3 arasında, A. baumannii izolatlarında imipenem direnci %10,4-98,9 ve meropenem direnci %7,6-98,9 arasında değişmektedir [4,5,8,[15][16][17][18][19][26][27][28][29][30][31]. Çalışmamızda P. aeruginosa suşlarında 2011 ve 2014 yıllarında imipenem direnci sırasıyla %45,4 ve %50, meropenem direnci sırasıyla %44,5 ve % %50,9 olarak saptanmış olup yıllar içinde istatistiksel olarak anlamlı bir değişiklik saptanmamıştır.…”
Section: Yöntemlerunclassified